Chronic Obstructive Pulmonary Disease Knowledge Analysis In High School Students (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
Smoking is one of the causes of premature death and disability, and one of the diseases caused by smoking is COPD. Chronic obstructive pulmonary disease (COPD) is a major worldwide leading cause of morbidity, mortality, and disability. It also becomes the serious healthcare system’s economic problem. By knowing the level of public understanding of this disease, we were able to find out what education could be given to increase COPD understanding. This study aims to determine the level of knowledge of high school students about COPD and to evaluate after being given a presentation about COPD. It is a descriptive study. The study had 95 participants and was conducted cross-sectionally. This study was conducted at the Zoom meeting on November 21, 2021. The data collection technique is that respondents filled out a Google Form. The subjects were 95 participants who had undergone COPD education, and there was a statistically significant difference in COPD knowledge before and after it (p0.01). Knowledge of COPD symptoms had the greatest significant influence on education (p0.01) of the COPD knowledge categories assessed.